Accelerated seam carving for image retargeting. Issue 6 (15th April 2019) - Patel, Diptiben; Raman, Shanmuganathan
Abstract : Display of images on different display devices having varied size and aspect ratio requires one to resize them. Many attempts have been made to perform content‐aware image retargeting while generating an image compatible with a target display size. Seam carving is one of the image retargeting operators which alters the size of an image by removing least energy pixels. However, it requires high computational time in order to perform retargeting. In this study, the authors accelerate the naive seam carving process by removal or insertion of multiple pixel wide batch seam in a single iteration rather than a single pixel wide seam. Along with the energy of pixels to be removed, inserted energy after the removal of a batch seam is also minimised in order to prevent the inclusion of false edges. The width of a batch seam is a critical factor which is made adaptive during the retargeting process to preserve the energy of an image. They have shown a significant decrease in computational time with the increase in the width of a batch seam. They have compared the proposed technique with other state‐of‐the‐art image retargeting operators using different quality assessment metrics and visual results.